2017
DOI: 10.1021/acsami.7b02075
|View full text |Cite
|
Sign up to set email alerts
|

Alkenyl Carboxylic Acid: Engineering the Nanomorphology in Polymer–Polymer Solar Cells as Solvent Additive

Abstract: We have investigated a series of commercially available alkenyl carboxylic acids with different alkenyl chain lengths (trans-2-hexenoic acid (CA-6), trans-2-decenoic acid (CA-10), 9-tetradecenoic acid (CA-14)) for use as solvent additives in polymer-polymer non-fullerene solar cells. We systematically investigated their effect on the film absorption, morphology, carrier generation, transport, and recombination in all-polymer solar cells. We revealed that these additives have a significant impact on the aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…We also investigated their device stability under continuous heating at 80 °C over 70 d. It is worth noting that residual additive 1,8-diiodooctane (DIO) within the film has been implicated as the cause of slow changes in morphology over time, which impact device performance and stability. [32][33][34] Thus we fabricated solar cell devices without using DIO to exclude the complication of additive. The resultant devices still exhibited comparable PCEs compared to the optimal devices using additive, [13] which makes it simpler to focus on the effect of blend ratio on the device stability under long-time thermal stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also investigated their device stability under continuous heating at 80 °C over 70 d. It is worth noting that residual additive 1,8-diiodooctane (DIO) within the film has been implicated as the cause of slow changes in morphology over time, which impact device performance and stability. [32][33][34] Thus we fabricated solar cell devices without using DIO to exclude the complication of additive. The resultant devices still exhibited comparable PCEs compared to the optimal devices using additive, [13] which makes it simpler to focus on the effect of blend ratio on the device stability under long-time thermal stress.…”
Section: Introductionmentioning
confidence: 99%
“…In this report, we compared the device performance of nonfullerene solar cells utilizing aforementioned polymeric and molecular acceptors with a wide range of blend ratios. We also investigated their device stability under continuous heating at 80 °C over 70 d. It is worth noting that residual additive 1,8‐diiodooctane (DIO) within the film has been implicated as the cause of slow changes in morphology over time, which impact device performance and stability . Thus we fabricated solar cell devices without using DIO to exclude the complication of additive.…”
Section: Introductionmentioning
confidence: 99%
“…Nonhalogenated solvents are discussed in Section . The molecular structures of some nonhalogenated additives are shown in Figure 23 …”
mentioning
confidence: 99%
“…Recent studies reported the use of acids polymers as dopants, to access and stabilize the electrically conducting states of conducting. The acids polymers are used for replace small-molecules acids as: poly(acrylic acid), poly(styrenesulfonate) (PSS), and poly(2-acrylamido-2-methyl-1-propanesulfonic acid), (2-acrylamido-2-methyl-1-propanesulfonic acid) (PAAMPSA), because its chemical nature, helps to stabilize the conduction of the polymers, in conclusion, the presence of an excess of carboxylic acid in the chemical structure promotes good dispersion, thus stabilizing the electric nature of the doped polymers [60].…”
Section: Polymermentioning
confidence: 99%